Phytochemical Investigation and Antibacterial Activity of Bergenia ligulata - Rajbhandari, M.; Khatri, H. R.; Lalk, M.; Gewali, M. B.; Lindequist, U. (Journal of Nepal Chemical Society, 2013)
In the course of screening of plant extracts for antimicrobial activity, the methanolic extract of Bergenia ligulata (Saxifragaceae) exhibited antibacterial activity against gram-positive bacteria. Fractionation of ethylacetate soluble phase of the methanol extract led to the isolation of bergenin (1), 11-O-p-hydroxybenzoylbergenin (2), 6-O-galloylarbutin (3) and epiafzelechin (4). Except bergenin, other compounds were isolated for the first time from B. ligulata. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8118 Journal of Nepal Chemical Society Vol. 28, 2011 Page: 110-114 Uploaded Date: May 24, 2013